#TITLE_ALTERNATIVE# - ASTARINADEA, RAHMI
Transmission process of dengue fever can be presented in a mathematical model as a non linear differential equations system. From this model of dengue transmission, the number of infected people (host population) by a time unit is influenced by the biting rate of the vector, such as Aedes aegypti , the transmission probability from vector to host, and the proportion of susceptible host in the whole of host population times with the number of infected vector. Biting rate of the vector and transmission probability from vector to host are parameters that will be estimated. These parameters are estimated using the Finite Element Method with Euler Method and Regularized Least Square, where daily new infected data is used. In this final project, the new infected data of dengue fever patient in Borromeus Hospital Bandung during 2008 is used to see the effectiveness of the method. The estimated parameters represent proportion of transmission probability from vector to host in the whole of host population and biting rate of the vector in a day can influence the number of infected people by the dengue fever. Relation between the estimated parameters with the number of infected people by the dengue fever can be measured by coefficient of correlation. From the numerical results we obtain positive linear relation between the estimated parameters and the infected people.